MobApp: A Data Visualization Tool for Trajectory Analysis - Cruz, Michael O.; Neto, Fernando; Barbosa, Luciano (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2023)
In this paper, we present a demo called MobApp, a data visualization application to facilitate spatio-temporal trajectories analysis. It aims to help domain analysts and practitioners/scientists to analyze and get insights from real-world trajectories. The tool supports: (1) exploratory analysis of trajectories, which allows users to visualize selected trajectories on a map and provides some statistics about trajectories’ points; (2) visualization of anomalous trajectories and the regions where the anomalies occur, detected by an anomaly detection model; and (3) evaluation of anomaly detection models to compare their performance.